(untitled) (British Journal of Global Ecology and Sustainable Development, 2024)
One of the most widespread types of applied arts is the art of painting, which appeared in ancient times and developed with the development of people’s consciousness. The interest in drawings led to the emergence of painting schools. Our master painters Komoliddin Behzod, Oqa Mirak, Shayhzoda Mahmud, Khudobergan Muhrkan, who contributed to the creation of the first painting schools, created their own schools.